Analysis of Preschool Curricula Amid Covid-19 Pandemic and Post-Pandemic Period - Fatih Selim Erdamar; Burhan Akpinar (UIN Sultan Aji Muhammad Idris Samarinda, 2022)
The purpose of this study was to examine the effects of the Covid-19 Pandemic on the implementation of the preschool curriculum from the perspective of teachers. The study, which was designed on a qualitative basis, was carried out with 31 preschool teachers determined with the purposeful sampling method. The data were collected via the interview form applied to the teachers who constituted the aforementioned study group. For the analysis of the data, content analysis was applied. For the analyses, the teachers’ views were gathered under certain headings and coded. In the coding made by using the frequency technique, which is the complement of the qualitative data, the coding technique was used in accordance with the concepts obtained from the data. By combining these codes, certain themes were created. Next, the themes were described and interpreted with tables for easy understanding and explanation in line with the purpose of the study, and conclusions were drawn accordingly. On the other hand, it was thought that in the study, the technological addiction in question might be caused by the unconscious and misuse of these technologies rather than by the educational technologies used extensively during the pandemic process. The teachers constituting the study group predicted that human dimensions such as psychological and personality dimensions, self-care skills, and behavioral problems would come to the fore in relation to the pre-school curriculum in the post-pandemic period.